A mathematical model of chemotherapy response to tumour growth - Pinho, Suani Tavares Rubim; Rodrigues, Diego Samuel [UNESP]; Mancera, Paulo Fernando de Arruda [UNESP] (My University, 2011)
A simple mathematical model, developed to simulate the chemotherapy response to tumour growth with stabilized vascularization, is presented as a system of three differential equations associated with the normal cells, cancer cells and chemotherapy agent. Cancer cells and normal cells compete by available resources. The response to chemotherapy killing action on both normal and cancer cells obey Michaelis-Menten saturation function on the chemotherapy agent. Our aim is to investigate the efficiency of the chemotherapy in order to eliminate the cancer cells. For that, we analyse the local stability of the equilibria and the global stability of the cure equilibrium for which there is no cancer cells. We show that there is a region of parameter space that the chemotherapy may eliminate the tumour for any initial conditions. Based on numerical simulations, we present the bifurcation diagram in terms of the infusion rate and the killing action on cancer cells, that exhibit, for which infusion conditions, the system evolves to the cure state. Copyright © Applied Mathematics Institute, University of Alberta.
Keywords: Chemotherapy; Mathematical model; Tumour growth